The Long Term Impact of French Settlement on Education in Algeria - Ouarda Merrouche (Uppsala University, Department of Economics, 2007)
This paper provides evidence on the long run relationship between European settlers presence and education levels in Algeria. To correct for endogenous sorting of settlers (and natives) into regions I rely on the fact that proximity to the Mediteranean coast determined the timing of conquest and therefore settlements size. The main finding indicates that the colonial policy of discrimination explains a large fraction of the disparities in literacy across regions through 1998.However this effect declines significantly over time. I point out three factors that may explain this declining effect: (1) the massive funds allocated to the education sector post-war; (2) the role of the market via migration; (3) social interaction effects whereby natives progressively adopted education and fertility norms of the settlers.
urn:nbn:se:uu:diva-25353
Keywords: I29; I38; O15; 330; French rule; Discrimination; Education; Social Interactions; Kolonialismus; Einwanderung; Franzosen; Bildungsinvestition; Bildungsniveau; Algerien